Associations between spleen volume and exercise capacity in advanced heart failure patients with left ventricular assist device. (25th November 2020) - Hiraiwa, H; Okumura, T; Sawamura, A; Kazama, S; Kimura, Y; Shibata, N; Arao, Y; Oishi, H; Kato, H; Kuwayama, T; Yamaguchi, S; Kondo, T; et al.
Abstract: Background: The spleen has been recognized as an important organ with several functions such as a reservoir of blood volume, and an involvement in iron metabolism by processing of aged red blood cells and recycling iron. During exercise, spleen contracts, and red blood cells pooled in the spleen are recruited into the systemic circulation. So far, we reported that spleen size changed in advanced heart failure (HF) with left ventricular assist device (LVAD). In addition, spleen volume was related to pulmonary capillary wedge pressure (PCWP) or right atrial pressure (RAP) as parameters of cardiac preload. However, it remains unclear about the relationship between spleen volume and exercise capacity in advanced HF with LVAD. Purpose: The purpose of this study was to investigate the associations between spleen volume and exercise capacity in advanced HF patients with LVAD. Methods: We enrolled 27 HF patients (21 males, 45±12 years) with LVAD (HeartMate II™; Abbott, Chicago, IL, USA) for use as a bridge to heart transplantation. All patients underwent blood test, echocardiography, right heart catheterization, computed tomography (CT) and cardiopulmonary exercise testing (CPET). Spleen size was measured by CT volumetry. We excluded patients with splenic infarction or aortic valve closure surgery. Results: At baseline, body mass index, blood brain natriuretic peptide levels, hemoglobin levels, left ventricular ejection fraction were 21.4±3.1 kg/m 2, 73.8 (51.9–165.8) pg/mL, 12.1 (10.6–13.4) g/dL, 24.8±14.7%, respectively. Total cardiac output (CO), the sum of pump flow and CO of native heart was 4.6±0.9 L/min, and spleen volume was 184.9±48.8 mL. As for parameters of CPET, peak heart rate (HR), peak VO2, and peak O2 pulse were 128±25 beats/min, 14.2±3.3 mL/kg/min, and 6.6±1.9 mL/beat. At rest, there were significant correlations between spleen volume and PCWP (r=0.382, p=0.049), RAP (r=0.406, p=0.035) or pulsatility index (r=0.384, p=0.047), despite no correlations with total CO or pump flow. During exercise, there were significant interrelations of spleen volume with peak VO2 (r=0.451, p=0.018) and peak O2 pulse (r=0.427, p=0.026). Furthermore, peak VO2 was interrelated with peak HR (r=0.481, p=0.011) or hemoglobin levels (r=0.649, p<0.001). Remarkably, spleen volume was significantly correlated with hemoglobin levels (r=0.391, p=0.043) (Figure). Interpreting these results based on Fick's formula, the proportion of native CO to total CO is very small at rest, but increases during exercise. The spleen during exercise may contribute to increased native CO, especially stroke volume. Moreover, the spleen may be related to both cardiac preload and oxygen carrying capacity, resulting in a significant association between spleen volume and peak VO2. Conclusion: Spleen volume could be a useful predictor of exercise capacity in advanced HF patients with LVAD, reflecting splenic function to modulate cardiac preload and blood hemoglobin levels. Funding Acknowledgement: Type of funding source: None